The Implementation Of Agile Methodologies In Developing A Back Office Application For Internal Operations: A Case Study Of Sukhakala Photobooth (PT. Smrta Amerta Adiwarna) - Christian Hartanto; Isti Raafaldini Mirzanti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to explore the application of Agile methodologies in the planning and development of a back-office application tailored for PT. SMRTA AMERTA ADIWARNA's Sukhakala photobooth operations. By addressing the company's challenges in operational efficiency, data accuracy, and real-time decision-making, this research outlines a strategic approach that integrates user-centered design principles with iterative development processes. The proposed back-office application is expected to enhance internal operations, improve financial management, and support strategic growth, ultimately contributing to the company's long-term success in a competitive market.